KARANTINA DAN HOSPITALITAS YANG BERESIKO Respons Gereja Di Sepanjang Sejarah Pandemi - Yohanes Krismantyo Susanta; Daniel Fajar Panuntun (Jurnal Lektur Keagamaan, 2021)
This paper discusses the hospitality of early Christians in the face of pandemics that have occurred throughout church history. A pandemic that lasts a long time and results in many deaths will cause mass hysteria. This was experienced by the global population at the end of 2019, namely the Covid-19 pandemic. Humanity is trying to overcome the spread of disease medically but also needs to be able to provide the right formulation of social attitudes in dealing with pandemics. The purpose of this paper is to find out the response of early Christians in the face of pandemics in the past and to draw theological reflections and lessons from church fathers regarding the Covid-19 pandemic. This paper uses a historical approach. Data collection was carried out through a study of literary criticism regarding the study of the history of the Church's history and the response of the Church Fathers in facing the pandemic in their respective times. This study finds that the history and responses of the church fathers emphasized the importance of quarantine and hospitality in dealing with the pandemics that occurred in their time. The implementation of this attitude is to emphasize the importance of quarantine and friendliness in dealing with the pandemic, including the current Covid-19 pandemic. Keywords: Church Fathers, Covid-19, Hospitality, Pandemic, Christian   Tulisan ini membahas tentang hospitalitas orang Kristen awal dalam menghadapi pandemi yang berlangsung di sepanjang sejarah gereja. Pandemi yang berlangsung lama dan mengakibatkan kematian dalam jumlah besar akan menimbulkan suatu histeria massal. Hal ini yang dialami oleh penduduk global pada akhir tahun 2019, yaitu pandemi Covid-19. Umat manusia berusaha mengatasi penyebaran penyakit tersebut secara medis, akan tetapi juga perlu mampu memberikan suatu rumusan sikap sosial yang tepat dalam mengatasi pandemi tersebut. Tujuan tulisan ini untuk mengetahui respons orang Kristen awal dalam menghadapi pandemi di masa lalu serta menarik refleksi teologis dan pelajaran dari Bapa-Bapa gereja terkait dengan pandemi Covid-19. Tulisan ini menggunakan pendekatan kualitatif dengan pendekatan sejarah. Pengumpulan data dilakukan melalui studi kritik literatur mengenai kajian sejarah Gereja dan respons Bapa-Bapa Gereja dalam menghadapi pandemi pada zamannya masing-masing. Kajian ini menemukan bahwa sejarah dan respons Bapa-Bapa gereja menekankan pentingnya sikap karantina dan hospitalitas dalam menghadapi pandemi yang berlangsung pada zamannya. Implementasi sikap ini untuk menekankan pentingnya karantina dan hospitalitas dalam menghadapi pandemi termasuk pandemi Covid-19 pada saat ini. Kata kunci: Bapa Gereja, Covid-19, Hospitalitas, Pandemi, Sejarah Kekristenan